Designing small-sided games for counter-attack training in youth soccer - Rochael, M.; Praça, G. M. (International Journal of Sports Science & Coaching, 2023)
The present study aimed to test different designs of counter-attacking training on tactical behaviour by manipulating the number of players and time pressure (limitation on the duration of the players` offensive action). Specifically, we compared the influence of time pressure and numerical superiority (through an additional player) on the players` performance and tactical behaviour in small-sided games (SSGs). Forty under-17 soccer athletes participated in the study. The athletes performed 4 SSGs in the following configurations: numerical equality and time pressure (GR-4 × 4-GR - TP); numerical equality and no time pressure (GR-4 × 4-GR - NTP); numerical superiority and time pressure (GR-5 × 4-GR - TP) and numerical superiority and no time pressure (GR-5 × 4-GR - NTP). Tactical performance was evaluated using the Game Performance Evaluation Tool (GPET), and tactical behaviour using positional data measured by the Global Positioning System. The statistical analysis was performed using two-way repeated measures analysis of variance. There was a better tactical performance in decision-making (0.669 ± 0.135, p = .02 and r = .27) and execution (0.602 ± 0.134, p = .002 and r = .44) of technical-tactical actions in the SSG without the time pressure rule. Furthermore, the space exploration index showed lower values (5.634 ± 0.604, p = .007 and r = .32) in games with time pressure than in games without this rule, and there were no significant differences for player length and width behaviour between protocols. It is concluded that the time pressure rule reduces the exploratory behaviour of the players. Understanding these effects allows coaches to plan better training sessions that address the contents of counter-attacks in SSG.